Complete response to avelumab and IL-15 superagonist N-803 with Abraxane in Merkel cell carcinoma: a case study. Issue 2 (10th September 2020) - Drusbosky, Leylah; Nangia, Chaitali; Nguyen, Andrew; Szeto, Christopher; Newton, Yulia; Spilman, Patricia; Reddy, Sandeep Bobby
Abstract : Merkel cell carcinoma (MCC) is a rare aggressive form of skin cancer originating in neuroendocrine cells. The antiprogrammed death ligand 1 (PD-L1) monoclonal antibody (mAb) avelumab has been approved for treatment of MCC, but options are limited, should it be ineffective as a monotherapy. Combined therapy with low/moderate dose nab-paclitaxel and an interleukin 15 (IL-15)-based therapeutic such as the IL-15 'superagonist' N-803 may increase response by activation of the immune system. The case of a 71-year-old man diagnosed with MCC who achieved and maintained a complete response (CR) by treatment with the anti-PD-L1 mAb avelumab in combination with IL-15 superagonist N-803 and nab-paclitaxel (Abraxane) is presented. Avelumab treatment alone resulted in a response in a para-aortic lesion, but not the other tumor masses. N-803 was added, followed by nab-paclitaxel; CT showed a decrease in the size of the abdominal mass at 1 month, near resolution at 3 months and CR at 5 months. Abraxane was discontinued after the first CR on CT, and the patient continues on avelumab/N-803 treatment and maintains a CR. Combination of avelumab with low/moderate-dose chemotherapy and an immune enhancer such as N-803 may offer a viable treatment option for MCC patients for whom avelumab therapy alone was not effective.